Synergistic Interaction of Fluconazole/Amphotericin B on Inhibition of Enzymes Contributes to the Pathogenesis of Candida Tropicalis - Alireza Khodavandi; Fahimeh Alizadeh; Mahsa Jafarzadeh (Tabriz University of Medical Sciences, 2018)
Background: Candidiasis has gained much attention in recent decades due to its increasing prevalence in immunocompromised patients. Usually, antifungals such as fluconazole and amphotricin B are used for treatment of candidiasis, but one of the major clinical problems is the emergence of antifungal resistance. Combination antifungal therapy is one of the most commonly used methods to alleviate the problem of antifungal resistance. Methods: The effect of fluconazole alone and in combination with amphotericin B on C. tropicalis isolates were performed using the Clinical and Laboratory Standards Institute (CLSI) reference method. Eventually hypha formation, time kill study, proteinase and phospholipase activity and expression of PLB and SAP2 genes were carried out to investigate the enzymes inhibitory properties of antifungal tested against C. tropicalis. Results: Results showed the significant synergic effect of fluconazole in combination with amphotericin B in inhibiting the growth of C. tropicalis isolates, with fractional inhibitory concentration indices ranging from 0.06 to 0.5. The combination of fluconazole with amphotericin B reduced the number of yeast form and inhibited the yeast to hyphae transition in C. tropicalis. The antifungals tested were able to show the effect of down regulating expression of the selected genes significantly in fluconazole/amphotericin B ranging from 1.42- to 2.27-fold. Conclusion: Our results demonstrated that the synergistic interaction of fluconazole/amphotericin B would be worth exploring for the management of candidiasis. In addition, PLB and SAP2 genes could be probable molecular targets in the synergistic interaction of fluconazole/amphotericin B in C. tropicalis.